Ovalbumin is synthesized in mouse cells transformed with the natural chicken ovalbumin gene. - Lai, E C (1980)
The entire chicken ovalbumin gene, accompanied by genomic DNA sequences flanking both termini of the gene and three copies of the herpes simplex virus thymidine kinase gene, has been cloned in plasmid pBR322. This recombinant plasmid was linearized and used to transform thymidine kinase-deficient mouse cells. Thymidine kinase-positive transformants were selected by their ability to grow in the hypoxanthin/aminopterin/thymidine (HAT) medium. The entire ovalbumin gene integrated into high molecular weight DNA within all the transformants and retained its original sequence organization. In all of the transformants examined, a protein identified as chicken ovalbumin by immunoreactivity was detected within the cells. It is estimated that between 1000 and 100,000 molecules of chicken ovalbumin were produced per mouse cell in each of these transformants. Our results demonstrate that the mouse cellular machinery can be utilized to accurately express genetic information encoded in a cloned gene from a different eukaryotic organism into its specific protein product.